2015
DOI: 10.1128/jb.02235-14
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FliL Alters Proteus mirabilis Surface Sensing and Temperature-Dependent Swarming

Abstract: Proteus mirabilis is a dimorphic motile bacterium well known for its flagellum-dependent swarming motility over surfaces. In liquid, P. mirabilis cells are 1.5-to 2.0-m swimmer cells with 4 to 6 flagella. When P. mirabilis encounters a solid surface, where flagellar rotation is limited, swimmer cells differentiate into elongated (10-to 80-m), highly flagellated swarmer cells. In order for P. mirabilis to swarm, it first needs to detect a surface. The ubiquitous but functionally enigmatic flagellar basal body p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 65 publications
2
35
0
Order By: Relevance
“…The location and structure of the additional ring are similar to those of the FliL ring found in B. burgdorferi (43,44). FliL has been shown to play important but diverse roles in many bacterial species (43,(45)(46)(47). The exact structure and function of FliL in H. pylori remain to be elucidated.…”
mentioning
confidence: 64%
“…The location and structure of the additional ring are similar to those of the FliL ring found in B. burgdorferi (43,44). FliL has been shown to play important but diverse roles in many bacterial species (43,(45)(46)(47). The exact structure and function of FliL in H. pylori remain to be elucidated.…”
mentioning
confidence: 64%
“…In addition, one flagellum-related protein was more abundant at −10°C 8 weeks: FliL ( Fig. Further, they demonstrated that the motility of ΔfliL is temperature dependent, suggesting that FliL interacts with a component of the motor involved in torque generation and helps maintain the integrity and stability of the flagellar rod (Lee and Belas, 2014). FliL is proposed to participate in the coupling of MotB with the flagellar rotor in an indirect fashion and is part of the basal flagellum complex (Suaste-Olmos et al, 2010).…”
Section: Flagellar Proteins and Motilitymentioning
confidence: 96%
“…revealed that FliL plays a role in sensing surfaces (Lee et al, 2013). Further, they demonstrated that the motility of ΔfliL is temperature dependent, suggesting that FliL interacts with a component of the motor involved in torque generation and helps maintain the integrity and stability of the flagellar rod (Lee and Belas, 2014). Because fliL defects yield species-specific phenotypic changes (Lee et al, 2013 and refs within), the exact role of the increased abundance of FliL in −10°C Cp34H cells needs to be examined further.…”
Section: Flagellar Proteins and Motilitymentioning
confidence: 99%
“…We further propose that novel and yet uncharacterized mechanisms exist to tune swarmer cell elongation and promote multicellular rafting based on integrated environmental cues. The motA-deficient strain failed to elongate, and flagellar activity is linked to swarmer cell development (40). Therefore, such unidentified mechanisms presumably function downstream of a theorized flagella-mediated surface-sensing switch.…”
Section: Discussionmentioning
confidence: 99%